2023
DOI: 10.1039/d3ta01820b
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic binding between an engineered interface and functionalized ferrocene offers remarkable charge extraction efficiency in lead halide perovskites

Abstract: Ferrocene derivatives have been recognized as a new hole-transporting layer (HTL), imparting stability, enhanced charge separation, and transport properties at the perovskite/HTL interface. Perovskite solar cells with functionalized ferrocene have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…This is why we have not observed any observable features for either ferrocene derivatives or the oxidized ferrocene derivatives in the TA spectrum . Nevertheless, in our earlier studies, we have shown a clear signature of oxidized ferrocene derivatives by recording the difference absorption spectrum at different times of visible-light exposure, where an increase in the absorbance in the 600–700 nm range could be assigned to the oxidized ferrocene derivatives. , …”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…This is why we have not observed any observable features for either ferrocene derivatives or the oxidized ferrocene derivatives in the TA spectrum . Nevertheless, in our earlier studies, we have shown a clear signature of oxidized ferrocene derivatives by recording the difference absorption spectrum at different times of visible-light exposure, where an increase in the absorbance in the 600–700 nm range could be assigned to the oxidized ferrocene derivatives. , …”
Section: Resultsmentioning
confidence: 52%
“…41 Nevertheless, in our earlier studies, we have shown a clear signature of oxidized ferrocene derivatives by recording the difference absorption spectrum at different times of visible-light exposure, where an increase in the absorbance in the 600−700 nm range could be assigned to the oxidized ferrocene derivatives. 36,72 Kinetic fits of the bleach recovery were analyzed, and the faster decay components (τ 1 ) were considered to deduce the timescales of the hole transfer from the band-edge states. 39 Figure 7a−c compares the bleach recovery of CsPbBr 3 in the absence and presence of FcA, FcUnA, and FcAm, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Perovskites have emerged as promising materials for photovoltaics, optoelectronics, photodetectors, and photocatalysis due to their high power conversion efficiency (PCE), low fabrication cost, and ease of processing. Their intriguing attributes, such as tunable and broad visible-light absorption, high absorption cross section, high photoluminescence quantum yield (PLQY), high defect tolerance, low excitonic binding energies, and long charge carrier diffusion length, make them ideal for light-harvesting applications. The optical properties of perovskite nanocrystals (PNCs) can be tuned by modulating their morphology or halide composition. Morphology influences the quantum confinement effect, providing opportunities to regulate excited-state dynamics. Understanding surface chemistry is essential for regulating the properties of PNCs, offering exciting prospects for researchers to unlock their full potential. Surface capping ligands, such as oleic acid (OA) and oleylamine (OAm), play a pivotal role in controlling surface chemistry and morphology. However, these ligands are monoamphiphilic, featuring anchoring groups at one end of the hydrocarbon/alkyl chain.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, nanocrystals (NCs) such as lead halide perovskites have garnered significant attention in the arenas of photovoltaics, micro-LEDs (LED = light-emitting diodes), and quantum dot (QD) displays. They exhibit unique optoelectronic properties, which give them an edge over traditional semiconductor NCs (TiO 2 , CdS, CdSe, etc.) and bulk semiconductors. Moreover, the ease of synthesis, wide absorption range over the visible spectrum, high photoluminescence quantum yields (PLQYs), long electron–hole diffusion length, and ease of halide diffusion allow tailoring of their photophysical properties and band structure to meet specific needs. , To date, their potential has been immensely realized as active materials in solar cells with efficiencies of over 25.6%. , …”
Section: Introductionmentioning
confidence: 99%
“…8,9 To date, their potential has been immensely realized as active materials in solar cells with efficiencies of over 25.6%. 10,11 However, translating their properties for application in catalysis is still in its infancy. A material deemed as a potential photocatalyst should have three essential properties: a high absorption coefficient spanning the visible-light region, which can then be extrapolated for solar energy capture, the generation of separable charge carriers, and redox ability.…”
Section: ■ Introductionmentioning
confidence: 99%